1999
DOI: 10.1021/bk-1999-0734.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides and Human Health: The Influence of Pesticides on Levels of Naturally-Occurring Plant and Fungal Toxins

Abstract: While the potential health risks from pesticide residues generate significant public, legislative, and regulatory concern, it is possible that agricultural pesticide use may, on occasion, influence dietary risks. It has been proposed that pesticide use may reduce the risks associated with naturally-occurring toxins of plants and fungi by reducing the pest pressures which may stress plants into producing their own toxins or by controlling the fungi responsible for mycotoxin production. Very little direct resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Winter (1999) published a review summarizing the influence of pesticides on the levels of naturally occurring toxins in food and concluded that very few studies had been conducted that directly related pesticide use to the levels of naturally occurring toxins, particularly in the case of plant secondary metabolites. The review cited examples showing reductions in mycotoxin levels in foods and fungal cultures treated with fungicides.…”
Section: Quality and Safety Comparisons Of Organic And Conventional Fmentioning
confidence: 99%
“…Winter (1999) published a review summarizing the influence of pesticides on the levels of naturally occurring toxins in food and concluded that very few studies had been conducted that directly related pesticide use to the levels of naturally occurring toxins, particularly in the case of plant secondary metabolites. The review cited examples showing reductions in mycotoxin levels in foods and fungal cultures treated with fungicides.…”
Section: Quality and Safety Comparisons Of Organic And Conventional Fmentioning
confidence: 99%
“…Measures to control disease include, sound crop rotation programs, development of resistant plant germplasm and application of nematicides (Chitwood 2002). However, nematicide application provokes undesired non-target effects, calling for plant disease management protocols based on biological resources (Winter 1999). AMF represents a well-known beneficial biological resource in relation to plant production in agroecosystems, where improved host plant nutrition and health are among the most important ecosystem services provided (Gianinazzi et al 2010).…”
Section: Introductionmentioning
confidence: 99%